Drug poisoning: a reason for care in a hospital emergencies unit. Issue 2 (12th March 2012) - Larrodé, I.; Real, J.M.; Garcés, C.; Alonso, Y.; Povar, J.; Abad-Sazatornil, M.R.
Abstract : Background: Intoxication by drugs requires often quick attention in the emergency department (ED), so an antidote kit to combat drug intoxication would be helpful. Purpose: To analyse intoxication by drugs treated in the emergency department as a preliminary step to making up an antidote kit. Materials and methods: All patients treated in ED for drug intoxication in a Spanish hospital were included, from January to June 2010. Data collected were: sex, age, cause, measures, days of stay in ED, admission, ward, duration of admission, complications. Results: Data from 137 patients were analysed, 79 females (57.7%), median (minimum-maximum) age was 37 (92–0) years. 77 patients (56.2%) were intoxicated by drugs affecting the central nervous system, 19 (13.9%) by analgesic/anti-inflammatory drugs, 11 (8.0%) by cardiovascular system drugs, 5 (3.6%) by systemic endocrine drugs and the drug(s) involved were unknown in 21 (15.3%) of cases. In 20.4% the intoxication was due to several drugs. 65.0% needed drug-specific treatment. Gastric lavage was necessary in 29.9%. In addition, activated charcoal was administered in 32.1%, flumazenil in 25.5%, naloxone in 4.4% and N-acetylcysteine in 4.4%. Other drugs used were norepinephrine, digoxin-specific antibody (Fab) fragments, a potassium chelator, antiemetics, blood coagulation factors and anticholinergics. The median stay in ED was 1 (0–2) day. 27 patients (19.7%) were admitted and 2 (1.5%) requested voluntary discharge. Of the inpatients, 26.9% were to the psychiatry ward, 19.2% to the critical care unit, cardiology and internal medicine wards, and 15.4% to the paediatric ward. The stay in hospital was 6 (17–0) days. Seven patients had complications related to intoxication (three acute kidney injury, two rhabdomyolysis, two aspiration pneumonia) but none of them died. Conclusions: The analysis of intoxications treated in ED will guide the contents of the antidote kit. It is important to increase the control of drugs that affect the central nervous system.